The impact of continuous cropping and intercropping of Scutellaria baicalensis on the growth of walnut seedlings and soil chemical properties - XIE Jiayi; WEI Changjiang; XU Haigen; SONG Jian; QI Jianxun; ZHANG Yunqi; ZHAI Changyuan; HOU Zhixia (Guoshu xuebao)
[Objective] Continuous cropping has a noticeable inhibitory effect on many crops, resulting in autotoxicity. There are few reports on whether walnut (Juglans regia L.) cultivation experiences continuous cropping obstacles. The study aimed to clarify the growth performance and mineral nutrient characteristics of walnut seedlings in continuously cropped soil, as well as the impact of intercropping walnut with scutellaria on its growth and soil properties in order to provide references for alleviating continuous cropping obstacles in walnuts and optimizing intercropping models. [Methods] This study employed a pot experiment using soil from a walnut grove where the walnut had been cultivated for 17 years (walnut soil) and soil from the same forest where the walnut had never been cultivated (regular soil) as the substrate. Four treatments were established: walnut soil-walnut sole cropping (HD), regular soil-walnut sole cropping (PD), walnut soil-walnut-scutellaria (Scutellaria baicalensis) intercropping (HJ), and regular soil-walnut-scutellaria intercropping (PJ). [Results] (1) Before planting, there were no significant differences between the two soil types in terms of total nitrogen, total phosphorus, total potassium, magnesium, copper, ammonium nitrogen, and pH value. However, the calcium, available phosphorus, quick-acting potassium, and electrical conductivity in the walnut soil were significantly lower than those in the regular soil, while the manganese content and organic matter content in the walnut soil were significantly higher than those in the regular soil. The correlation analysis showed that the available phosphorus in the soil was significantly and positively correlated with the relative chlorophyll content of the walnut leaves, and significantly and negatively correlated with the manganese content in the walnut roots. The quick-acting potassium in the soil was significantly and positively correlated with the number of branches of the walnut trees and extremely significantly and positively correlated with the leaf area, with an r value of 0.997 4. The manganese content in the walnut roots was significantly and negatively correlated with the plant height and ground diameter, and extremely significantly and negatively correlated with the relative chlorophyll content of the leaves. It would be possible that the imbalance of available elements and the accumulation of manganese might be limiting factors for the growth of walnut under continuous planting. (2) Under the walnut soil treatment, the height, ground diameter, biomass, leaf area, number of branches, and relative chlorophyll content of the walnut seedlings were all significantly lower than those under the regular soil treatment, the walnut soil would reduce the walnut's ability to accumulate nitrogen, phosphorus, potassium, and calcium. The continuous planting caused lower level of the potassium content in the walnut leaves than the regular soil. The correlation analysis showed that the potassium content in the walnut leaves was significantly and positively correlated with the and plant height, ground diameter, leaf area, and quick-acting potassium, and extremely significantly positively correlated with the number of branches, with an r value of 0.995 6. The continuous cropping led to an imbalance in the available potassium in the walnut soil, which reduced the leaf absorption of potassium, thus limiting the development of the walnut. After four months of planting, the total nitrogen, total phosphorus, calcium, and organic matter content in the regular soil were lower than those in walnut soil, while the available phosphorus and quick-acting potassium content were significantly higher. (3) The intercropping walnut with Scutellaria baicalensis had a certain promoting effect on the walnut seedling growth. The intercropping significantly increased the nitrogen, phosphorus, and calcium content and accumulation in the walnut roots, while reducing the accumulation of the magnesium, copper, and manganese. It also significantly increased the levels of the available phosphorus, organic matter, and alkaline phosphatase activity in the soil. The soil alkaline phosphatase activity was extremely significantly and positively correlated with the nitrogen and phosphorus content in the walnut roots, indicating that the increase in the soil alkaline phosphatase activity under intercropping also enhanced the walnut roots' ability to absorb nitrogen and phosphorus. The intercropping also improved the activity of the sucrase, which was significantly and positively correlated with the calcium content in the walnut roots, indirectly affecting the calcium absorption by the roots. The improvement of the soil enzyme activity promoted the accumulation of nitrogen, phosphorus, and calcium in the walnut roots and reduced the manganese and copper content in the walnut seedlings and roots. [Conclusion] In the soil where the walnut had been continuously planted for 17 years, the growth and nutrient absorption of the walnut seedlings were inhibited, as evidenced by the significant reductions in the plant height, trunk diameter, biomass, leaf area, and branch number. The continuous planting resulted in a decrease in the available phosphorus, available potassium, and electrical conductivity in the soil, and increase in the manganese content. This significantly affected the potassium absorption capacity of the walnut leaves, leading to an increase in manganese accumulation and calcium content in the leaves. The intercropping significantly enhanced the levels of the available phosphorus, organic matter, soil pH, and alkaline phosphatase activity in the soil, improving the nitrogen, phosphorus, and calcium content and enrichment in the walnut roots, while reducing manganese content in the walnuts and copper content in the roots. Therefore, the intercropping management may provide a more favorable soil environment for the healthy growth and nutrient absorption of the walnut seedlings. The study would offer a practical reference for the intercropping model of walnuts and S. baicalensis.